CEDAW Perspective on Legal Protection for Women Victims of Honor Killing in Pakistan - Rahel Elena Gultom; Muhammad Alvi Syahrin; Masdar Bakhtiar (Jurnal Dinamika Hukum, 2025)
Despite being a Muslim country, Pakistan still has laws that discriminate against women, especially when it comes to their status as victims of assault. An example is the honor killing that occurred in this country, which is a very crucial event. This research aims to ensure and analyze the protection of women's human rights and Pakistan's legislative framework. In this research, normative legal research is used to analyze the provision of legal protection to women who are victims of honor killings in Pakistan. This research analyzes the perspective of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) to provide answers on the formulation of the problem put forward in this research. Using this research methodology, it was determined that several reasons contributed to the incomplete implementation of legal regulations related to establishing women's human rights in Pakistan, including the lack of adequate legal enforcement, ingrained patriarchal culture and customs, and lack of knowledge. among women themselves about their rights. Additionally, there is evidence of substandard implementation of CEDAW, acts of discrimination against women, and cases of honor killings signed by Pakistan. Meanwhile, the CEDAW articles set out rules regarding how women's rights should be realized.